General Risk on Trust, and The Intention to Recommend Halal Food: A Millennial Perspective - Siti Maysyaroh (Halal Tourism and Pilgrimage, 2023)
The purpose of this study is to investigate the influence of generalized risk on halal consumer trust, satisfaction and intention to recommend halal food from a millennial perspective. Understanding how millennials perceive halal food as critical and socially influential consumers is crucial in the face of growing demand for halal food products in the global market. In an effort to achieve the objectives of this study, the Structural Equation Model Partial Least Square (SEM-PLS) method was used to analyze data collected through an online survey of a sample of millennials who are potential consumers of halal food. Data for this study were collected through a questionnaire survey distributed to 191 millennial consumers of halal products. Analysis of the structural equation model shows that general risk has a significant and positive effect on trust, satisfaction, and intention to recommend halal food, while trust and intention to recommend are negatively and insignificantly related. These findings suggest that it is important to reduce common risks associated with halal food to increase millennials' trust and satisfaction as consumers. This research contributes to the understanding of millennial consumer behavior related to halal food and provides guidance for halal food industry players in increasing consumer loyalty and the effectiveness of their marketing strategies. By understanding the factors that influence trust, satisfaction and intention to recommend, industry players can design more effective programs and campaigns in reaching and meeting the needs of millennials as halal food consumers.